1998
DOI: 10.1037/0033-295x.105.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines for psychologists: Implications of bidirectional immune-to-brain communication for understanding behavior, mood, and cognition.

Abstract: The brain and immune system form a bidirectional communication network in which the immune system operates as a diffuse sense organ, informing the brain about events in the body. This allows the activation of immune cells to produce physiological, behavioral, affective, and cognitive changes that are collectively called sickness, which function to promote recuperation. Fight-flight evolved later and coopted this immune-brain circuitry both because many of the needs of fight-flight were met by this circuitry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
702
5
20

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,013 publications
(739 citation statements)
references
References 180 publications
(203 reference statements)
12
702
5
20
Order By: Relevance
“…These findings replicate the results of many previous studies, which demonstrated that activation of the immune system by LPS, as well as other immune challenges, induces a reduction in appetite and body weight, suppres- sion of locomotor, exploratory, and social activity, fatigue and malaise, impairment in cognitive abilities, reduced libido and sexual behavior, and anhedonia (Anisman and Merali 1999;Dantzer et al 1999;Maier and Watkins 1998;Yirmiya 1996;Yirmiya et al 1994Yirmiya et al , 1999. Our results also demonstrate that LPS produced a marked depletion of CRH-41 ME content, which reflects its release into the portal vessels (Chappell et al 1986), with a concomitant elevation in plasma corticosterone levels.…”
Section: Discussionsupporting
confidence: 90%
“…These findings replicate the results of many previous studies, which demonstrated that activation of the immune system by LPS, as well as other immune challenges, induces a reduction in appetite and body weight, suppres- sion of locomotor, exploratory, and social activity, fatigue and malaise, impairment in cognitive abilities, reduced libido and sexual behavior, and anhedonia (Anisman and Merali 1999;Dantzer et al 1999;Maier and Watkins 1998;Yirmiya 1996;Yirmiya et al 1994Yirmiya et al , 1999. Our results also demonstrate that LPS produced a marked depletion of CRH-41 ME content, which reflects its release into the portal vessels (Chappell et al 1986), with a concomitant elevation in plasma corticosterone levels.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, proinflammatory cytokines, one of the key chemical messengers of the immune system, not only orchestrate peripheral inflammatory responses to prevent infection (such as in response to a microbial antigen), but these cytokines also signal the brain to alter behavior. Specifically, through a variety of mechanisms, including activation of afferent vagal nerves (ie, proinflammatory cytokines bind to cells of the vagal paraganglia and activate the vagal nerve; Goehler et al, 1997) and transport through the blood-brain barrier (BBB; Dantzer et al, 2008;Maier and Watkins, 1998), cytokines can signal the brain to invoke a constellation of behaviors known as sickness behaviors (Hart, 1988;Dantzer, 2001;Kelley et al, 2003;Quan and Banks, 2007). These behaviors include loss of appetite, sleepiness, social withdrawal, fatigue, increased pain, and anhedonia, and are conceptualized as a coordinated motivational response thought to facilitate recuperation and recovery from illness and disease (Dantzer and Kelley, 2007;Hart, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Nevertheless, over the last two decades there have been studies suggesting that systemic cytokines may access the brain and affect brain function by either overcoming the blood-brain barrier through limited diffusion or saturable transport systems 18 or via direct sensory nerve connections from the periphery. 19 Other than its effectiveness for neuroregulatory actions after the intra-cerebral administration of cytokines, 20,21 there was, however, no specific marker to demonstrate and confirm a direct CNS action for IFN-a following systemic peripheral administration.…”
Section: Introductionmentioning
confidence: 99%